Atividade antihelmíntica do “Parabendazole” em ovinos de Uruguaiana, naturalmente infestados - Santos, Virginio Teixeira dos (Revista do Centro de Ciências Rurais, 2007)
In the present paper are reported the anthelmintic activity of “PARABENDAZOLE” in critical trial carried in naturally infested sheeps in Uruguaiana, Rio Grande do Sul, Brasil.